Accelerating Universe with Viscous Cosmic String in Quadratic Form of Teleparallel Gravity: Accelerating Universe with Viscous Cosmic String - Bhoyar, S. R.; Chirde, V. R.; Shekh, S. H. (Journal of Scientific Research, 2019)
In this paper, we have investigated Kantowaski-Sachs cosmological model with bulk viscous and cosmic string in the framework of Teleparallel Gravity so called f(T) gravity, where T denotes the torsion scalar. The behavior of accelerating universe is discussed towards the particular choice of f(T) = Α(T) + β(T)m. The exact solutions of the field equations are obtained by applying variable deceleration parameter which is linear in time with a negative slope. The physical behavior of these models has been discussed using some physical quantities. Also, the function of the torsion scalar for the universe is evaluated.